Ponoszenie porażek sposobem na zdobywanie wiedzy - Kuśmierek, Anna (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The aim of the article is to defend the thesis that the worked through failure affects the development of a person through getting to know oneself and exploring the knowledge in the area where it is insufficient. The article states that failure is unavoidable, therefore from childhood a person should be taught to perceive it as a natural phenomenon. It is worth teaching children to see failure as a positive phenomenon as well, not just a negative one. When teaching children and young people, one should ensure the child’s development by adapting the methods of work to the student’s abilities and talents. A teacher, teaching children and youth to accept failure, should implement various educational methods. The contemporary model of working with children and youth offered by professional literature, presents a way of working with gifted students and students with educational problems. Methods of working with an average student are not developed. Besides, the model of working with a student is designed to result in his/her success. These studies suggest that failure is only a negative phenomenon, and that success is a positive one. The article also highlights learning from failure, which teaches coping skills for adult life.